Soft-shelled turtles of the family Trionychidae in South Asia: A review of studies on their biogeography, diversity, and conservation - Safi, Amtyaz; Kanwar, Roohi; Hashmi, Muhammad Usman Ali; Karl, Hans-Volker; Tichy, Gottfried; Rao, R. J. (Nepalese Journal of Zoology, 2025)
There are 30 species of soft-shelled turtles belonging to the family Trionychidae worldwide. Nine species and five genera of this family are native to South Asia. All soft-shelled freshwater turtle species of this family in South Asian countries are listed in the IUCN Red List. The authors review the existing literature, discuss the findings, and suggest integrating ecological and bio-molecular concepts to understand soft-shelled turtles in South Asia. These turtles play a vital role in the health of aquatic ecosystems because they are both scavengers and omnivores, providing a mechanism for dispersing plants, purifying water by removing carrion, and contributing to the overall health of these ecosystems. These turtles are a source of food and ingredients in Chinese medicine and Oriental pharmacopeia. Their populations are declining due to the large-scale usage of these turtles for various purposes and habitat degradation.